A Case Report on Neuro-Retinitis - Pathak, Dr. Meenal; Chaudhary, Dr Priyanka; Karandikar, Dr Sumita; Punjabi, Dr Sneha (Journal of Biomedical and Pharmaceutical Research, 2023)
Neuroretinitis is an inflammation of the neural retina and optic nerve. It was originally described by Leber in 1916 as a "stellate maculopathy," but this definition was challenged by Don Gass in 1977, citing that disc oedema precedes macular exudates. Subsequently, Gass confirmed optic disc leakage by fluorescein angiography and suggested the term "neuro retinitis." More recent retinal and optic nerve imaging has supported Gass' description. The condition was renamed Leber’s idiopathic stellate neuroretinitis. Neuroretinitis is characterized by an optic disc vasculature inflammation with fluid exudation into the peripapillary retina. The lipid-rich component of the exudate is further able to penetrate the outer plexiform layer, creating what is clinically seen as a macular star pattern. Only the aqueous phase is then able to pass through the external limiting membrane to accumulate beneath the neurosensory retina. Neuroretinitis is a type of optic neuropathy characterized by an acute unilateral visual loss in the setting of optic disc swelling accompanied by hard exudates characteristically arranged in a star shape around the fovea. It is classified as one form of optic neuritis, the other forms being the more common retrobulbar neuritis and papillitis. Funduscopically, neuroretinitis is often confused with hypertensive, renal and infiltrative retinopathies as well as with papillitis, papilledema, anterior ischemic optic neuropathy and retinal vein occlusion. It is an entity that physicians, paediatricians and neurologists are poorly exposed to since the diagnosis and management are almost exclusively performed by the ophthalmologist. Pathogenesis and aetiology of neuroretinitis are distinctly different from other funduscopic ally-resembling conditions often encountered by neurologists during their training and clinical practice; further, these have different principles of management and prognosis. The prognosis for visual recovery is reported to be excellent, although not uniform. It affects persons of all ages, more often in the third and fourth decades of life, with no gender predilection. Visual acuity at the time of initial examination ranges from 6/6 to light perception (PL). It can manifest either due to systemic infections, autoimmune diseases or as idiopathic.